Elephantiasis Nostras Verrucosa of Lower Limb: a Case Report - Amir Kalafi (Acta Medica Iranica, 2014)
Elephantiasis nostras verrucosa (ENV) is a rare condition in which hyperkeratosis, fibrosis and disfiguration of dermis occurs. It is caused mostly by non infectious diseases such as surgery, trauma, tumors, and venous obstructions. To our knowledge there is not any case report of ENV in Middle East region. In this patient, ENV caused by trauma and Patient presented with enlargement of right lower limb.